2013
DOI: 10.1021/am403449j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mobility and Reactivity of Water Molecules on TiO2 Nanoparticles by 1H Solid-State Nuclear Magnetic Resonance

Abstract: Understanding interfacial water behavior is essential to improving our understanding of the surface chemistry and interfacial properties of nanomaterials. Here using 1H solid-state nuclear magnetic resonance (1H SSNMR), we successfully monitored ligand exchange reaction between oleylamine (OLA) and adsorbed water on titanium dioxide nanoparticles (TiO2 NPs). Three different types of interfacial waters with different reactivities were distinguished. The mobility of the adsorbed water molecules was characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 41 publications
4
28
0
Order By: Relevance
“…As mentioned previously, a simple and green way to fabricate TiO 2 NPs with uniform particle size and high surface hydroxyl groups is absolutely required for industrial production. On the basis of the results of this study and the literature [20,43,49,50,51,52,53,54,55,56], a pictorial representation of the structure of water layers adsorbed on the surface of TiO 2 NPs is proposed in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned previously, a simple and green way to fabricate TiO 2 NPs with uniform particle size and high surface hydroxyl groups is absolutely required for industrial production. On the basis of the results of this study and the literature [20,43,49,50,51,52,53,54,55,56], a pictorial representation of the structure of water layers adsorbed on the surface of TiO 2 NPs is proposed in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…similar to the three-domain models (with irreversibly bound waters, partially mobile waters, and bulk waters) that have been used to interpret solid-state nuclear magnetic resonance (NMR) data for hydrated TiO 2 nanoparticles. 10,63 The total hydration layer thickness (defined as the difference in positions of the outermost L i -peak and the top oxygen layer in the TiO 2 slab) is 5 to 7.5 Å for the different surfaces (Fig. 5), with anatase (100) being a notable exception, as discussed below.…”
Section: Hard and Soft Hydration Layersmentioning
confidence: 93%
“…7,8 Understanding water adsorption on TiO 2 is the key not only to efficiently split water molecules (as made use of in hydrogen gas production 9 ) but also to optimize adsorption on, and functionalization of, TiO 2 by larger molecules as mediated via strongly bound surface waters. [10][11][12][13][14][15] On the other hand, concerns have been raised with respect to environmental safety and health when TiO 2 is used in medical implants 16 and as engineered nanoparticles in consumer products. 17 TiO 2 nanoparticles are small enough to penetrate the blood-brain barrier, 18 can aggregate in organisms and the environment, and yield a nanotoxic response by increasing the levels of intracellular reactive oxygen species, leading to apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22). 32,33 For example, Zhang et al 34 found low Ti coordination numbers (5.1 vs. 6 for bulk) for small-sized (2 nm) amorphous nanoparticles using synchrotron wideangle X-ray scattering (WAXS) and molecular modeling. Much less is known about the irregular surfaces of wet nanoparticles, where the higher frequency of surface defects may lead to higher reactivity.…”
Section: Introductionmentioning
confidence: 99%